Explaining complexity to power. A failed mission? - Gloria Regonini (International Review of Public Policy)
To revisit Bruno Dente's extraordinary research path is also an exploration of the development of policy studies in Italy from the 1970s to Dente’s final experiments aimed at improving the quality of interaction between policymakers and policy researchers. At the heart of Dente’s scientific vision lie theories and methods of policy evaluation that are sensitive to two different sources of complexity: the nature of policy problems and the relationship between the evaluator and the evaluated. For this reason, I focus on policy evaluation to explain the social, cultural, and political context of his enterprise. For our generation, public policy research was a discovery of the American policy sciences of democracy – a single trajectory from evaluation to the essence of democracy, something that was entirely original in the landscape of the then nascent discipline of political science in Italy. I then jump forward 50 years to offer a critical assessment of policy evaluation in Italy in light of Bruno’s vision. Here the comparison of Italy with France shows the different path to the institutionalization of evaluation, showing that little or nothing of what Bruno envisioned has been embedded in Italian institutions. This has happened because of limitations and deficiencies not only in the demand for policy evaluation, but also on the supply side. This conclusion sheds light on the breadth of policy vision, but also on the critical variables that engaged researchers have to take into account when moving from research to practice and to the impact on political institutions.